Development of a gastroschisis core outcome set - Allin, B; Hall, N; Ross, A; Marven, S; Kurinczuk, J; Knight, M (BMJ Publishing Group, 2018)
Objective Outcome reporting heterogeneity impedes identification of gold-standard treatments for children born with gastroschisis. Use of core outcome sets (COS) in research reduces outcome reporting heterogeneity and ensures that studies are relevant to patients. The aim of this study was to develop a gastroschisis COS. Design and Setting Systematic reviews and stakeholder nomination were used to identify candidate outcomes that were subsequently prioritised by key stakeholders in a three-phase online Delphi process and face-face consensus meeting using a nine-point Likert scale. In phases two and three of the Delphi process, participants were shown graphical and numerical representations of their own, and all panels scores for each outcome respectively and asked to review their previous score in light of this information. Outcomes were carried forward to the consensus meeting if prioritised by two or three stakeholder panels in the third phase of the Delphi process. The COS was formed from outcomes with consensus meeting scores ≥70% 7–9 and <15% 1-3. Results 71 participants (84%) completed all phases of the Delphi process, during which, 87 outcomes were assessed. Eight outcomes, mortality, sepsis, growth, number of operations, severe gastrointestinal complication, time on parenteral nutrition, liver disease and quality of life for the child met criteria for inclusion in the COS. Conclusions Eight outcomes have been included in the gastroschisis COS as a result of their importance to key stakeholders. Implementing use of the COS will increase the potential for identification of gold standard treatments for the management of children born with gastroschisis.